Sistem Informasi Bimbingan Konseling Pada SMA 4 Bandar Lampung Menggunakan Metode Certainty Factor - Septiono Septiono; Machudor Yusman; Yodhi Yuniarthe (Universitas Mitra Indonesia, 2022)
At this time, student delinquency, which is increasing due to not being able to adapt to various social changes, is not a disease or problem that must be avoided but must receive special attention and guidance. With the counseling guidance software as a medium of consultation for students who can accommodate students who do not want to do guidance with the BK teacher. The knowledge obtained is student problems consisting of being late for school, truancy, broken home students, inferior, online game addicts, promiscuity, lack of motivation to learn, cheating, not being smart, sleeping in class. This consultation media is built using the certainty factor method which is a parameter value to show the amount of trust. This consultation media will provide several questions related to the cause of the problem that will be selected by the student (user) to obtain the results of the consultation. The advantage of using the certainty factor method is that the user can find out the certainty value of the conclusion of the problem obtained.